A Novel Idea Researching Transformative Learning in Fiction - Lawrence, Randee Lipson; Cranton, Patricia; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2015)
Lawrence and Cranton present a unique research methodology involving fictional characters as research participants. Transformative learning themes are identified through a content analysis of six contemporary novels. The characters from these novels are invited to come to a virtual space, the Butterfly Café where they engage in a series of dialogues on the research themes related to their transformative learning experiences. Each of the dialogues is followed by a debriefing session to deepen the understanding of the original themes Readers are given a window into Lawrence and Cranton’s analysis and interpretive process as they engage in dialogue with Celie from the Color Purple, Macon from Accidental Tourist, Mariam and Laila from A Thousand Splendid Suns, and others. The dialogues become a story within the stories told in the novels. The end product is the introduction of a new model of transformative learning based on a metaphor of planting, cultivating, and growing seeds. Central to the model is becoming conscious, a process that appeared in each of the novels. Readers will find insights into transformative learning that are outside of the standard academic treatment of the topic. Moving the research into the realm of fiction provides the opportunity for a creative exploration of transformative learning. Yet, since fiction inevitably mirrors reality, readers will be able to relate the analysis, the dialogues, and the ensuing model to their own lives and to their adult education practice.
Keywords: Education; Education, general